Aplikasi Pemesanan dan Pengelolaan Data Pada Gudang Kerupuk GG Purwokerto - Vadlya Maarif Vadlya; Hidayat Muhammad Nur; Mikhael Edwin Aditya (Informatics and Computer Engineering Journal, 2023)
A warehouse is a room that is used to store various kinds of goods and types in large quantities. Seeing this, the potential for the GG Kerupuk Warehouse Data Management and Ordering System is made, namely making the ordering process, data management and warehouse reports. This study used the prototype software development method and in addition to the data collection method. In the software development method with a prototype model to design an ordering system and warehouse data management, while the data collection method is used to gather the requirements of the information system to be created. The data processed in this system design contains client table data, orders, types of goods, payment transactions, transaction details, admin, super admin, incoming stock, outgoing stock, suppliers, goods table, purchases, returns, and reports. The results of this study are a prototype of an ordering information system and data management which is expected to help the activities of the warehouse system to be better and more effective and web-based computerized.